New Challenges and New Perspectives on Cooperativism and Development - Monroy Flores, Verel Elvira (Cooperativismo & Desarrollo, 2014)
Various proposals arise from this issue of the journal Cooperativismo y Desarrollo, which point to the discussion about new challenges and perspectives regarding cooperativism and development. Conventional development models, which have only generated erosion in the structures and systems within Latin America, are being questioned, so that with respect to the Western idea of development, alternatives arise that rescue the wisdom, customs and dialogs that mainly come from the original peoples of the South of the continent.